Preconditioning and postconditioning: from bench to bedside - Hausenloy, Derek J.; Yellon, Derek M. (SA Heart Journal, 2017)
Coronary heart disease (CHD) is the leading cause of death world-wide. Since 1990, more people in the world have diedfrom CHD than from any other disease (World Health Organisation, WHO). “Conditioning” the heart to render it more resistant to the detrimental effects of acute ischaemia-reperfusion injury harnesses the endogenous ability of the heart to protect itself. This can be achieved using various mechanical strategies including the application of brief episodes of ischaemia and reperfusion to either the heart itself (ischaemic preconditioning) or an organ/tissue remote from the heart (remote ischaemic preconditioning) prior to the sustained ischaemic insult. Importantly, this form of protection can be mimicked by pharmacological agents capable of recapitulating the protective effect of IPC(pharmacological preconditioning). Preconditioning-induced cardioprotection is clearly restricted to patients undergoing an anticipated ischaemic insult such as in patients undergoing cardiac surgery. In contrast, the other major form of “conditioning” termed postconditioning can be implemented in patients presenting with an acute myocardial infarction after the onset of the sustained ischaemic insult. In this setting, myocardial reperfusion is interrupted with intermittent short-lived episodes of myocardial ischaemia applied to the heart itself (ischaemic postconditioning) or an organ or tissue remote from the heart (remote ischaemic postconditioning) – an effect which can again be mimicked by pharmacological agents (pharmacological postconditioning).This article will briefly review these various forms of“conditioning” examining the underlying mechanistic pathways and their clinical application.